Differences in reasons for little cigar/cigarillo use across white and black/African American young adult users. (July 2021) - Dunn, Delaney S.; Johnson, Amanda L.; Sterling, Kymberle L.; Cohn, Amy M.
Highlights: There are racial discrepancies in reasons for little cigar/cigarillo (LCC) use. Black LCC users are more likely to report affordability as a reason for use. Product flavoring is the most popular reason for LCC use among White users. Abstract: Introduction: The prevalence of little cigar and cigarillo (LCC) use among young adults is high. Research shows there are racial/ethnic differences in this prevalence, with Black/African American users more likely to report current LCC use. Given these discrepancies in LCC use, the present study aimed to assess potential differences in reasons for LCC use between White and Black/African American young adult ever and past 30-day users. Methods: Participants were White (n = 2150), and Black/African American (n = 308) young adults (aged 18 to 24) recruited from Amazon Mechanical Turk who completed an online survey of tobacco use (December 2018–January 2019). LCC users were asked eight reasons for using LCCs. Results: Flavoring was cited as the most popular reason for LCC use among White ever users while affordability was the most popular among Black/African American ever users. Adjusted logistic regressions among ever users revealed that Black/African American respondents (vs White) were more likely to use LCCs because of their affordability, the perception that LCCs are less harmful than cigarettes, and because of LCC advertising appeal. Among past 30-day users, adjusted logistic regression models showed that Black/African American respondents (vs White) were more likely to use LCCs because of their affordability. Conclusions: Findings align with previous studies showing that LLCs are more heavily marketed in predominantly Black/African American communities. Prevention efforts should account for racial differences in reasons for use in message development.